2019
DOI: 10.1126/sciadv.aax9586
|View full text |Cite
|
Sign up to set email alerts
|

Blocking FcRn in humans reduces circulating IgG levels and inhibits IgG immune complex–mediated immune responses

Abstract: The neonatal crystallizable fragment receptor (FcRn) functions as an intracellular protection receptor for immunoglobulin G (IgG). Recently, several clinical studies have reported the lowering of circulating monomeric IgG levels through FcRn blockade for the potential treatment of autoimmune diseases. Many autoimmune diseases, however, are derived from the effects of IgG immune complexes (ICs). We generated, characterized, and assessed the effects of SYNT001, a FcRn-blocking monoclonal antibody, in mice, nonhu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(128 citation statements)
references
References 63 publications
3
119
0
6
Order By: Relevance
“…Thus, a clinical precedent for applying enzymatic IgG degradation to promote rapid and transient antibody clearance already exists. Further, it is noteworthy to mention that other orthogonal methods to facilitate IgG clearance using soluble antibody binding bacterial proteins (e.g., Protein M(40)), FcRn (neonatal Fc receptor) domains(41), anti-FcRn antibodies such as Rozanolixizumab(42), SYNT001(43, 44) etc have shown promise in the clinic as well.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a clinical precedent for applying enzymatic IgG degradation to promote rapid and transient antibody clearance already exists. Further, it is noteworthy to mention that other orthogonal methods to facilitate IgG clearance using soluble antibody binding bacterial proteins (e.g., Protein M(40)), FcRn (neonatal Fc receptor) domains(41), anti-FcRn antibodies such as Rozanolixizumab(42), SYNT001(43, 44) etc have shown promise in the clinic as well.…”
Section: Discussionmentioning
confidence: 99%
“…Single TEAE reports considered possibly related to efgartigimod and temporally associated with its administration included decreases in total lymphocyte counts, T lymphocytes and B lymphocytes, and monocytes, and an increase in neutrophil counts (Table I). [18][19][20][21][22][23][24][25] Hematologic changes (ie, abnormal differential WBC counts) observed in 3 patients following treatment with efgartigimod were mild and asymptomatic, and most likely explained by concomitant use of immunosuppressants. However, the first-in-human (FIH) study of efgartigimod 23 also reported abnormal differential WBC counts (mild decrease in CD8, CD3, CD56, CD4, and CD19 lymphocyte counts) after receipt of the drug (3 of 4 healthy volunteers who received 25 mg/kg and 4 of 4 who received 50 mg/kg).…”
Section: Lysosomal Degradationmentioning
confidence: 99%
“…Dose-dependent decreases in serum IgG concentration were observed by day 8, with the 20 mg/kg (n 5 12) single-dose group achieving its nadir of a 60% mean change from baseline in total serum IgG at this time point, whereas the 5 3 4 mg/kg (n 5 15) group achieved its nadir of 43.6% change from baseline on day 29. Nipocalimab (M281), a high-affinity, fully human monoclonal IgG 1 anti-FcRn antibody engineered to have no Fc effector potential (no C1q binding, and no binding to activating FcgR), and orilanolimab (SYNT001), a humanized IgG 4 k mAb, are 2 additional FcRn inhibitors with published FIH data 18,25 ( Table I). Nipocalimab is currently in phase 2 trials for autoimmune hemolytic anemia, hemolytic disease of the fetus and newborn, and MG.…”
Section: Lysosomal Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel molecules, referred to as "antibodies that enhance IgG degradation" or "Abdegs" (210), that bind to the FcRn with a higher affinity than IgG and in a pH-independent manner, have recently been generated. Moreover, FcRn-blocking monoclonal antibodies, such as Rozanolixizumab (211), SYNT001 (212), M281 (213) and Efgartigimod (214) are currently in phase 2 or 3 clinical trials (NCT04200456, NCT03075878, NCT04119050, NCT04225156). These molecules hold promise for the treatment of IgG-mediated diseases such as systemic lupus erythematosus, myasthenia gravis or immune thrombocytopenic purpura (210,215).…”
Section: Saturation Of the Igg Recycling Pathwaymentioning
confidence: 99%